2018
DOI: 10.3390/atmos9020039
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Wind Environment and Indoor/Outdoor Relationships for PM2.5 in Different Building–Tree Grouping Patterns

Abstract: Airflow behavior and indoor/outdoor PM 2.5 dispersion in different building-tree grouping patterns depend significantly on the building-tree layouts and orientation towards the prevailing wind. By using a standard k-ε model and a revised generalized drift flux model, this study evaluated airflow fields and indoor/outdoor relationships for PM 2.5 resulting from partly wind-induced natural ventilation in four hypothetical building-tree grouping patterns. Results showed that: (1) Patterns provide a variety of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…When the air exchange frequency is constant, airflow discharges rapidly, removing pollutants and reducing indoor particulate matter. Previous studies have demonstrated that absolute or relative difference in wind pressure in buildings is weakly correlated with indoor particle concentrations [58,88]. Our simulation results indicate that the natural ventilation rate is significantly and positively correlated with indoor particle concentration linked to window opening size.…”
Section: Resultssupporting
confidence: 54%
“…When the air exchange frequency is constant, airflow discharges rapidly, removing pollutants and reducing indoor particulate matter. Previous studies have demonstrated that absolute or relative difference in wind pressure in buildings is weakly correlated with indoor particle concentrations [58,88]. Our simulation results indicate that the natural ventilation rate is significantly and positively correlated with indoor particle concentration linked to window opening size.…”
Section: Resultssupporting
confidence: 54%
“…All metrics obtained were within the allowable ranges, indicating the models could suitably reproduce the actual environment of street canyon (Table 1). Additionally, the present authors compared this model with a wind tunnel experiment from a previous study that also showed that this model could accurately represent the actual street canyon environment [41]. The model was built according to site dimensions.…”
Section: Model Validationmentioning
confidence: 99%
“…To investigate the effects of GRs and GWs on PM 10 concentration distributions in different street canyon configurations, street canyon aspect ratios (H/W) were set to 0.5, 1.0, and 2.0. Since the dust-retaining ratio of the building envelope was low, it was treated as a solid block without consideration of dust retention and wind penetration [41]. Herbaceous plants are generally used for GWs with a height of 0.1-0.5 m [42].…”
Section: Numerical Model Settingmentioning
confidence: 99%
“…Hong et al [10] present results obtained from CFD simulations to determine the effects of four typical building-tree grouping patterns on the outdoor wind environment and the indoor/outdoor relationships for PM 2.5 as a result of partly wind-induced natural ventilation in Beijing; the relationship between the resulting wind pressure differences and indoor PM 2.5 concentrations; and which building-tree grouping pattern could provide the best ventilation potential or provide the lowest indoor PM 2.5 concentrations. Results clearly indicate that airflow and indoor/outdoor PM 2.5 dispersion strongly depend on the relationships of building layouts, tree arrangements, and orientation towards the prevailing wind.…”
Section: Relationship Between Indoor and Outdoor Ventilationmentioning
confidence: 99%